A Review: Design and Fabrication of Gas Sensor using Sol-Gel Spin Coating Technique for the Detection of Ethanol - Praveen J, Sangeetha S V, Shilpa N, Samarth Jain, Sangamesh S K (International Journal of Advanced Science and Technology, 2020)
The sensor is an important part of daily activity. The sensor has already been commonly used for a variety of various applications such as medical technology, aerospace, etc. In manufacturing, on the other hand, the devices are used to analyze certain ambient parameters including temperatures, humidity, etc. Gas sensors are one of these groups, used to detect the existence of gases. Most factories manufacture ethanol as one of their bi-products. Ethanol induces skin inflammation and triggers asthma to people employed in business, and drug misuse influences the actions of consumers that intensify society's crime and injuries. The largest proportion of ethanol is present in alcoholic drinks. Therefore, it is important to keep track. Because of the tremendous motivation in nanotechnology over time, gas sensors are chosen to identify gases. In the paper, a survey has been done on various gas sensors and concluded that zinc oxide thin film has been structured and manufactured using a novel method of sol-gel to recognize ethanol vapors at RT. Thin-film deposition can be achieved in two ways i.e. chemical vapor deposition (CVD) and physical vapor deposition (PVD). CVD is favored in dealing with low-cost chemical solutions. Using Scanning Electron Microscope (SEM) the structural and morphological characteristics can be analyzed. Various sensing parameters such as reaction time, sensitivity and recovery period can be calculated at room temperature. Keywords: Substrate, sol-gel, ZnO thin film, ethanol vapor, sensing parameters.